KEEFEKTIFAN PENGGUNAAN MEDIA ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Zeta, Naqimatuz; Thamrin Hidayat, Muhammad; Lutfauziyah, Asmaul; Wahyudi, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of snakes and ladders learning media in improving third-grade students’ learning outcomes in Natural and Social Sciences (IPAS). The study employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The participants consisted of 29 third-grade students of SDN Siwalankerto II Surabaya. Data were collected through tests, observations, and documentation. Tests were used to measure cognitive learning outcomes through pretests and posttests, while observations were used to assess psychomotor learning outcomes. Data were analyzed using the N-Gain test and Wilcoxon Signed Rank Test. The results showed that the average pretest score of 53.79 increased to 94.14 on the posttest. The N-Gain analysis yielded an average score of 0.86, categorized as high improvement. In addition, psychomotor learning outcomes achieved an average score of 94.17, categorized as very good. The Wilcoxon Signed Rank Test showed a significance value of 0.000 < 0.05, indicating a significant improvement in learning outcomes after the implementation of the snakes and ladders learning media. Therefore, snakes and ladders learning media is effective in improving students’ learning outcomes in elementary school IPAS learning.